PENGARUH KESADARAN WAJIB PAJAK, KETEGASAN SANKSI DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK BADAN DI KPP MAKASSAR SELATAN - Asrini Asrini (Bongaya Journal for Research in Accounting (BJRA), 2019)
:The purpose of this study was to determine whether awareness of taxpayers, firmness of sanctions, and services of Fiscus has a positive and significant impact on compliance of corporate taxpayers in South Makassar KPP both partially and simultaneously. Data obtained from 100 respondents registered as Corporate Taxpayers at the Makassar South Tax Office. Data collection is done through interviews, questionnaires and observations. The data analysis technique used in this research is multiple linear regression. Based on the results of the analysis it can be seen that the awareness of taxpayers and Fiscus Services has a positive and significant effect while the firmness of sanctions is not a significant positive effect on corporate taxpayers compliance in South Makassar KPP